Ultrasound, laboratory and histopathological insights in diagnosing papillary thyroid carcinoma in a paediatric population: a single centre follow-up study between 2000-2022 - Januś, Dominika; Wójcik, Małgorzata; Taczanowska-Niemczuk, Anna; Kiszka-Wiłkojć, Aleksandra; Kujdowicz, Monika; Czogała, Małgorzata; Górecki, Wojciech; Starzyk, Jerzy B. (Frontiers in Endocrinology, 2023)
Papillary thyroid carcinoma (PTC) often coincides with autoimmune thyroiditis (AIT); whether this association is incidental or causal remains debated. To evaluate the ultrasonographic, laboratory, and histopathological features of PTC in paediatric patients with and without AIT and its relationship to puberty. Patients and methods: A retrospective analysis of medical records of 90 patients (69; 76.7% females). The mean age at PTC diagnosis was 13.8 years [range 6-18]. All patients were evaluated ultrasonographically before thyroid surgery. Thyroid nodules were categorised using the European Thyroid Imaging Reporting and Data System (EU-TIRADS PL), and cytopathology was assessed using Bethesda criteria. Neck ultrasound results and thyroid and autoimmune status were correlated with histopathological PTC assessment. The coexistence of PTC and AIT was found in 48.9% (44/90) of patients. The percentage of AIT was increasing with age; AIT was present only in 1/3 of prepubertal, close to 50% in pubertal, and over 60% in adolescent patients. The youngest patients (aged <10 years old) presented more often with goitre and lymphadenopathy and less often with AIT than adolescents (15-18 years of age). There were no differences in TPOAb, TgAb, and TSH levels between the age subgroups. Presurgical TgAb levels were higher than those of TPOAb in the youngest patients. Histopathological analysis revealed that the solid subtype was observed more often in prepubertal children and diffuse sclerosing in children below 14 years of age, whereas the classic subtype dominated in late pubertal. Univariate and multivariate analyses revealed that lymph nodes metastases (LNM) were associated with PTC diameter and fT4 level, whereas extrathyroidal extension with age and angioinvasion with PTC diameter and age. The correlations between age and fibrosis, and psammoma bodies were close to significant. We did not observe an association between TSH levels and the presence of autoimmunity and PTC variables. In paediatric patients the natural course of PTC may be less aggressive in adolescent patients than in younger children (especially < 10 years of age). We suggest that pre-operative evaluation of paediatric patients with thyroid nodules could include apart from assessment of thyroid hormones, evaluation of TPOAb, TgAb, and TRAb together with comprehensive neck ultrasonography.